Identification of Transcription Factors for Lineage-Specific ESC Differentiation - Yamamizu, Kohei; Piao, Yulan; Sharov, Alexei A.; Zsiros, Veronika; Yu, Hong; Nakazawa, Kazu; Schlessinger, David; Ko, Minoru S.H. (Stem cell reports, 2013)
A network of transcription factors (TFs) determines cell identity, but identity can be altered by overexpressing a combination of TFs. However, choosing and verifying combinations of TFs for specific cell differentiation have been daunting due to the large number of possible combinations of ∼2,000 TFs. Here, we report the identification of individual TFs for lineage-specific cell differentiation based on the correlation matrix of global gene expression profiles. The overexpression of identified TFs—Myod1, Mef2c, Esx1, Foxa1, Hnf4a, Gata2, Gata3, Myc, Elf5, Irf2, Elf1, Sfpi1, Ets1, Smad7, Nr2f1, Sox11, Dmrt1, Sox9, Foxg1, Sox2, or Ascl1—can direct efficient, specific, and rapid differentiation into myocytes, hepatocytes, blood cells, and neurons. Furthermore, transfection of synthetic mRNAs of TFs generates their appropriate target cells. These results demonstrate both the utility of this approach to identify potent TFs for cell differentiation, and the unanticipated capacity of single TFs directly guides differentiation to specific lineage fates. •Lineage-determining single TFs are identified based on the correlation matrix•A proof of concept is demonstrated for ESC differentiation by 21 TFs•TFs orchestrate global gene expression changes via direct binding to target genes•Transfections of synthetic TF mRNAs generate desired differentiated cells Here, Ko and colleagues report that the correlation matrix of global gene expression profiles can identify individual TFs whose overexpression directs efficient, specific, and rapid differentiation into myocytes, hepatocytes, blood cells, and neurons. These results demonstrate that the unanticipated capacity of single TFs directly guides differentiation to specific lineage fates.